The Determinants of Participation in Non-Mandatory Training - Renaud, Stéphane; Lakhdari, Mehdi; Morin, Lucie (Relations industrielles / Industrial Relations, 2004)
This article presents an empirical research on the determinants of employees’ participation in non-mandatory training offered by their employer. The analysis model identified two groups of determinants, i.e. socio-demographic (age, gender, family responsibilities and education level) and employment-related (organizational tenure, hierarchical position and employment status). Participants, mostly female, were employees from a large Canadian service organization. Results showed that age negatively influenced participation, that women participated more than men, and that the education level was negatively related to participation. Findings also indicated a non-linear relationship between organizational tenure and participation, and that the probability of participation in non-mandatory training increased with the hierarchical position occupied. Family responsibilities and employment status were not found to be significant predictors of participation.